Pemberdayaan Ekonomi Masyarakat Berbasis Dana Sosial Keagamaan di Temanggung - Waluyo; Indah Piliyanti (Transformatif : Jurnal Pengabdian Masyarakat, 2023)
Dukuh Kandangan, in Tempuran Temanggung Village, consists of 130 families consisting of Christians, Muslims and Buddhists and live in harmony. The livelihoods of the majority are farmers and traditional ranchers. This community service is a form of support for strengthening religious moderation by empowering the community's economy based on socio-religious funds. Asset-based community development is used as a basis for the development of economic-based community empowerment. This approach focuses on developing community-based assets to support activities. This activity began with a focus group discussion (FGD) with academics to discuss the potential for community-based economic development in Temanggung. The results of this FGD were used to carry out interventions in the form of giving livestock which were managed by the community of three different religions in Dukuh Kandangan. These livestock become community assets to be jointly managed and used for the benefit of community capacity building.